Hubungan Gaya Belajar melalui Media Activity Group 3D dengan Kreativitas Peserta Didik dalam Bidang Desain Grafis pada Program Kesetaraan Paket A di PKBM Think Indonesia School - Fatimatuszzahro, Syahrina Laila; Yulianingsih, Wiwin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to determine the relationship between learning styles and students' creativity in the field of graphic design in the package A equivalency program at PKBM Think Indonesia School. This type of research uses correlational research with a quantitative approach. The population in this study were students from grades 5 to 6, totaling 30 students in the package A equivalency program at PKBM Think Indonesia School. Data collection techniques were carried out using questionnaires and documentation. Questionnaires and documentation to obtain data on students' learning styles and creativity. The data used to test the hypothesis is data on the creativity and learning styles of 3D activity group students at PKBM Think Indonesia School. The results of this study indicate that N=30 can be obtained. The result is that there is a significant correlation between learning style and creativity, which is indicated by the correlation coefficient number rxy = 0.604 which is greater than the r table at the 5% significance level = 0.361, which means r counting > r table, namely 0.604 > 0.361. Apart from that, it is known that the significance value increases to 0.000 where the teirseibuit number is less than 0.05 (<0.05), meaning that the hypothesis in this research is that there is a relationship between learning styles through 3D activity group media and students' creativity in the field of designing in the program. equality of package A at PKBM Think Indonesia School.